2019
DOI: 10.3389/fpsyg.2019.01335
|View full text |Cite
|
Sign up to set email alerts
|

Polyculturalism and Attitudes Toward the Continuing Presence of Former Colonizers in Four Postcolonial Asian Societies

Abstract: Polyculturalism is the lay belief that cultures are dynamically interconnected and mutually influencing each other historically and in contemporary times. Belief in polyculturalism is associated with various positive intergroup outcomes in intercultural social contexts, but it has never been studied in relation to intergroup attitudes in postcolonial societies. Two studies with participants from four postcolonial Asian societies (total N = 1,126) explore whether polyculturalism will also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Therefore, such potential difficulties associated with polyculturalism may be resolved by adopting a “neutral” form of polyculturalism or one that highlights both the positive interactions, commonalities, and influences among groups while also acknowledging any negative interactions in past discourses (Rosenthal & Levy, 2010). Ample research shows that such approach is associated with reduced hostility, resentment, or resistance, leading to higher quality intercultural contact and greater comfort with and appreciation for diversity (e.g., Bernardo et al, 2013, 2019; Rosenthal & Levy, 2012, 2016; Virgona & Kashima, 2021). Not “sugar coating” past intercultural relations might also be perceived more genuine than superficial and may also be the most practical and realistic given mixed discourses among groups in many countries.…”
Section: Practice Implications and Strategies To Foster Connectivitymentioning
confidence: 99%
“…Therefore, such potential difficulties associated with polyculturalism may be resolved by adopting a “neutral” form of polyculturalism or one that highlights both the positive interactions, commonalities, and influences among groups while also acknowledging any negative interactions in past discourses (Rosenthal & Levy, 2010). Ample research shows that such approach is associated with reduced hostility, resentment, or resistance, leading to higher quality intercultural contact and greater comfort with and appreciation for diversity (e.g., Bernardo et al, 2013, 2019; Rosenthal & Levy, 2012, 2016; Virgona & Kashima, 2021). Not “sugar coating” past intercultural relations might also be perceived more genuine than superficial and may also be the most practical and realistic given mixed discourses among groups in many countries.…”
Section: Practice Implications and Strategies To Foster Connectivitymentioning
confidence: 99%
“…It was also the only condition that produced a significantly different effect on the dependent variable when compared to the polyculturalism condition during the mediation analysis. This instant is worth exploring because it contradicts with the previous research that compared these two ideologies together where polyculturalism manipulation had mostly associated with intergroup attitude scores more than other ideologies (Bernardo et al, 2019;Bernardo et al, 2016;Bernardo & Presbitero, 2017;Cho et al, 2017;Cho et al, 2018;Rosenthal & Levy, 2012;.…”
Section: Effects Of Different Intergroup Ideology Manipulations On Th...mentioning
confidence: 59%
“…Empirically, many studies that compared these three ideologies together provided consistent results (Bernardo et al, 2019;Bernardo et al, 2016;Bernardo & Presbitero, 2017;Cho et al, 2017;Cho et al, 2018;Rosenthal & Levy, 2012;. Starting with colorblindness, the studies reported either statistically insignificant correlations with both multiculturalism and polyculturalism (Cho et al, 2017) or significantly low negative correlations with them (Cho et al, 2018).…”
Section: Comparing Colorblindness Multiculturalism and Polyculturalismmentioning
confidence: 86%
See 2 more Smart Citations